EXPLORING DIGITAL ASSESSMENT LITERACY IN MALAYSIAN ESL TERTIARY INSTITUTION INSTRUCTORS’ INNOVATIVE PEDAGOGY - Ameera Irdena Suyansah; Noraini Said; Esther Jawing (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This conceptual paper aims to study the digital assessment literacy of ESL instructors in Malaysia. In education, assessment is one of the most crucial components in the teaching and learning process. Assessment allows the instructors to gather information of the students to determine the students’ knowledge and to make improvements based on the data collected. With the digitalisation in education, it has propelled the relevancy of digital assessment. Despite the increasing use of digital assessments in educational settings, many educators lack the necessary digital assessment literacy skills to effectively create, administer, and interpret these assessments. Therefore, this study aims to explore the digital assessment literacy of ESL instructors. This study will use semi-constructed interview and analysis of documents. The type of sampling employed in this study is purposive sampling towards 15 ESL instructors in Malaysian Universities. The data will be analysed using thematic analysis. The expected result from this study is that ESL instructors will have knowledge of digital assessment but have areas of improvement in doing digital assessment. The researchers acknowledge that knowing how to use digital assessment tool is not sufficient, and teachers need to remain aware of how these tools are successful or unsuccessful. It is hoped that the outcome of this research will help the teachers to be knowledgeable in how they understand, conduct, and interpret digital assessments